How does Nogo receptor influence demyelination and remyelination in the context of multiple sclerosis? - Rashidbenam, Zahra; Ozturk, Ezgi; Pagnin, Maurice; Theotokis, Paschalis; Grigoriadis, Nikolaos; Petratos, Steven (Frontiers in Cellular Neuroscience, 2023)
Multiple sclerosis (MS) can progress with neurodegeneration as a consequence of chronic inflammatory mechanisms that drive neural cell loss and neuroaxonal dystrophy in the central nervous system. Immune-mediated mechanisms can accumulate myelin debris in the disease extracellular milieu during chronic-active demyelination that can limit neurorepair/plasticity and experimental evidence suggests that potentiated removal of myelin debris can promote neurorepair in models of MS. The myelin associated inhibitory factors (MAIFs) are integral contributors to neurodegenerative processes in models of trauma and experimental MS-like disease that can be targeted to promote neurorepair. This review highlights the molecular and cellular mechanisms that drive neurodegeneration as a consequence of chronic-active inflammation and outlines plausible therapeutic approaches to antagonize the MAIFs during the evolution of neuroinflammatory lesions. Moreover, investigative lines for translation of targeted therapies against these myelin inhibitors are defined with an emphasis on the chief MAIF, Nogo-A, that may demonstrate clinical efficacy of neurorepair during progressive MS.